PENINGKATAN KEPUASAN DAN KEPERCAYAAN PUBLIK: BERDASARKAN PRESPEKTIF KUALITAS PELAYANAN DAN KOMITMEN (Studi Pada Pemerintahan Desa/Kelurahan Se-Kecamatan Wangi-Wangi Selatan) - Rusfiadi Rusfiadi; La Hatani; Nursaban Rommy Suleman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The purpose of this research is to examine and explain the increase in public satisfaction and trust: based on the perspective of service quality and commitment. The design of this study is a positivist paradigm with a quantitative approach. Data collection was carried out in a cross-sectional manner using an instrument in the form of a questionnaire. The population of this study was village/kelurahan government officials in the Wangi-Wangi Selatan sub-district as many as 291 people. The sample size of this study can be determined using the Slovin formula, the number of samples obtained is 74 people. The sampling technique of this study was carried out randomly based on proportional random sampling of each village. The analytical tool used for hypothesis testing is Partial least square (PLS). The  results  show  that  the  quality  of  public  services  has  a  positive  and significant effect on public commitment and trust, but on public satisfaction it has no significant effect. User commitment has a positive and significant effect on public trust, but on the contrary, public trust has no significant effect on organizational commitment. The results of this study can prove that user commitment does not have a reciprocal effect on public satisfaction. Furthermore, user commitment to public satisfaction has a positive and significant effect, on the contrary, public satisfaction has a positive and significant effect on user commitment. Public trust has a reciprocal effect on public satisfaction. These results prove that public trust has a positive and significant effect on  public  satisfaction. On  the  other  hand,  public  satisfaction has  a  positive  and significant effect on public trust. The results of this study are also evidenced by the description of the respondents' statements on the variables of service quality, user commitment, trust and public satisfaction that have been carried out well in village/kelurahan governments in Wangi-Wangi Selatan District, Wakatobi Regency.